From late adolescence to young adulthood - Brockman, David (London : Karnac Books, 2011)
'By focusing on the transition from late adolescence to young adulthood, this innovative book makes a unique and valuable contribution to our understanding of a neglected area of development. Drawing on his extensive clinical experience with this age group as well as his understanding of the complex cultural and social forces that impinge on young people today, Brockman has produced that rarest of volumes: a work that is engaging, creative and wise while at the same time being eminently practical and useful. Addressing issues that are highly relevant to our older patients as well as our younge.
Cover; Copy Right; Content; Acknowledgments; Introduction; Chapter 1. Psychoanalytic Assessment of Young Adults; Chapter 2. Identity; Chapter 3. Gender and Sexual Identity; Chapter 4. Intimacy; Chapter 5. The Fate of Don Juan: The Myth and the Man; Chapter 6. The Power Motive in Late Adolescence and Young Adulthood; Chapter 7. Narcissistic Rage in Young Adulthood: The Tragedy of Akhilleus; Chapter 8. Creativity in the Young Adult: A Partial Review and a Critique; Chapter 9. Summary and Conclusions.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Adolescent psychiatry; Adolescent analysis; MEDICAL / Mental Health; MEDICAL / Psychiatry / General; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Mental Illness; PSYCHOLOGY / Psychopathology / General; Electronic books